The determinants of co2 emissions in Malaysia: A new aspect - Chin, Mui Yin; Puah, Chin Hong; Teo, Cia Ling; Joseph, Justina (Econjournals, 2018)
In light of the deterioration of environmental quality, this study aims to identify the determinants of CO2 emissions in Malaysia using the autoregressive distributed lag and the decomposition-type threshold methods. This study signifies that economic growth is the main contributor to CO2 emissions which is in line with the theory of the Environmental Kuznets Curve curve. Meanwhile, this study also confirms that vertical intra-industry trade between Malaysia and China together with the bilateral FDI from China to Malaysia are the significant determinants of CO2 emissions in Malaysia. As such, this study suggests that the Malaysian government should monitor the implementation of the green growth strategy to enhance the sustainability of the economic and trade growth without compromising environmental quality. © 2018, Econjournals. All rights reserved.